2017
DOI: 10.1007/s13669-017-0187-1
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis: Epidemiology, Diagnosis and Clinical Management

Abstract: Purpose of review Endometriosis is a disease of adolescents and reproductive-aged women characterized by the presence of endometrial tissue outside the uterine cavity and commonly associated with chronic pelvic pain and infertility. Here we review the epidemiology of endometriosis as well as potential biomarkers for detection and with the goal of highlighting risk factors that could be used in combination with biomarkers to identify and treat women with endometriosis earlier.. Recent findings Early age at me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
459
3
29

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 483 publications
(502 citation statements)
references
References 99 publications
11
459
3
29
Order By: Relevance
“…In particular, at outpatient gynecologic clinics, the diagnosis may be based on symptoms and the results of internal examination and TV-US [7]. Oral contraceptives are often the first-line treatment for endometriosis when patients are relatively young and unmarried [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, at outpatient gynecologic clinics, the diagnosis may be based on symptoms and the results of internal examination and TV-US [7]. Oral contraceptives are often the first-line treatment for endometriosis when patients are relatively young and unmarried [7].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, at outpatient gynecologic clinics, the diagnosis may be based on symptoms and the results of internal examination and TV-US [7]. Oral contraceptives are often the first-line treatment for endometriosis when patients are relatively young and unmarried [7]. Epidemiological studies have shown that oral contraceptives prevent ovarian cancer and the risk decreases further as the age of starting contraceptive therapy declines and the duration of treatment increases [8].…”
Section: Discussionmentioning
confidence: 99%
“…Time since the last birth increases the risk of uterine fibroids and multiparity exerts a protective effect . Early age at menarche increases the risk of endometriosis, while parity is associated with a decreased risk …”
Section: Epidemiological Evidencementioning
confidence: 99%
“…11 Early age at menarche increases the risk of endometriosis, while parity is associated with a decreased risk. 12 At any age above 30 years, women who have never conceived have a lower probability of achieving a pregnancy compared with women with prior fertility. 13…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…Endometriosis is endometrium-like tissue outside uterus with similar response towards steroid hormone. [1][2][3][4] Endometriosis prevalence is approximately 5-10% of general population and it reached up to 50% in infertile women. The point prevalence of endometriosis (n = 6146, mean age 40.4±8.0 years) was 10.8 per 1000 (95% CI 10.5-11.0).…”
Section: Introductionmentioning
confidence: 99%